KULAK .ID: AN INNOVATIVE SITE TO INTRODUCE SMES TO ECONOMIC SUSTAINABILITY BASED ON VILLAGE POTENTIAL - Yuli Agustina; Heri Pratikto; Madziatul Churiyah; Andi Basuki (Transpublika Publisher, 2024)
Kulak.id is an innovative platform designed to empower Small and Medium Enterprises (SMEs) by promoting economic sustainability based on the unique potential of villages. This initiative leverages local resources and capabilities, enabling SMEs to thrive within their communities while contributing to the broader economic landscape. The platform serves as a bridge between traditional village industries and modern market demands, offering tools and support for businesses to enhance their operations and reach. By focusing on the inherent strengths of village economies, Kulak.id not only fosters sustainable business practices but also preserves and revitalizes local cultures and industries. The ultimate goal of Kulak.id is to create a resilient and self-sufficient economic environment for SMEs that can adapt and flourish in the face of global challenges.